The totalitarian situation responsible for snowfall in the city of Baghdad on 11, February 2020 - Mahmoud, Ammar Yassir (Al-Adab Journal, 2021)
Snow fell in some parts of Iraq, including the city of Baghdad, on February 11, 2020, which is a rare phenomenon. It became clear through the analysis of the weather maps that the merging of the separate center of the sub-polar of low pressure area with the Sudanese low pressure area was the main factor in the occurrence of this phenomenon and its depth, which reached a height of (1470) meters, It was accompanied by the existence of a cold clouds troughs within the level of (500) millibars, which reached a height of (5400) meters, and the polar air pressure played a role in the emergence of the upper troughs and surface troughs where the air pressure is lower than that surrounding locations relative to the study area, where low pressure from under area of wind that occur in the upper levels, which leads to the growth of troughs and heights on the surface. It also studied the weather conditions associated with snowfall, represented by (temperature, wind direction, wind speed, air pressure, relative humidity, clouds).